The Grain of Dust: A Novel - Phillips, David Graham, 1867-1911; Wenzell, A. B. (Albert Beck), 1864-1917 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Grain of Dust: A Novel" by David Graham Phillips is a work of fiction written during the early 20th century. The novel introduces its readers to the contrasting lives of two characters: Miss Dorothea Hallowell, an unassuming young woman seeking employment, and Frederick Norman, a young and ambitious lawyer in a prestigious law firm. The narrative explores themes related to social class, ambition, and the complexities of human relationships. The opening of the novel presents the mundane circumstances under which Dorothea finds herself working at a large law firm in New York City. Her interactions are minimal, hinting at her self-effacing nature and the struggles she faces as a temporary employee. In contrast, Frederick Norman emerges as a dynamic character, displaying wit, ambition, and a certain ruthlessness in his professional ambitions. The reader witnesses their initial encounter, which is laden with an undercurrent of potential emotional complexity that might develop as the story unfolds. As Dorothea's character slowly reveals depth through her emotional struggles, Norman$1 (Bs allure as both a charismatic leader and an enigmatic figure becomes apparent, setting the stage for their developing relationship. (This is an automatically generated summary.)s
Release date is 2004-12-15
Produced by Charles Keller and David Garcia
Keywords: Love stories; Man-woman relationships -- Fiction